Where to flee? Preferences for host communities among displaced people in Congo - Nik Stoop; Peter Van der Windt; Sigrid Weber (PLoS ONE, 2025)
Previous research has explored host communities’ attitudes toward displaced individuals, but much less is known about what displaced people seek in a host community. Understanding both perspectives is key to fostering successful local integration. We address this gap through a randomized conjoint experiment in which nearly 2,000 respondents in the Kasai region of the Democratic Republic of Congo - internally displaced persons (IDPs), returned IDPs, repatriated refugees, and members of the host community - evaluated hypothetical host communities, imagining where they would prefer to settle if forced to flee. Results indicate that, beyond safety, respondents prioritize job opportunities while also valuing social networks and political participation. Preferences are largely similar across groups. The findings suggest that the promotion of economic opportunities and inclusive governance are among the most effective strategies to create conditions conducive to local integration.